Pemanfaatan Akar Serat Bambu Terhadap Campuran Aspal AC-WC - Rio Rahma Dhana (Universitas Islam Lamongan, 2022)
The purpose of this study was to determine whether the roots of bamboo fiber can be mixed with asphalt which is adhesive (waterproof) and an alternative to overcome the problem of road damage. The process of mixing bamboo root fiber with AC-WC asphalt is carried out during the frying process with the aggregate, then after the frying process is carried out the pounding process is carried out (compact), then let stand and after cooling the mashall test process is carried out. Effect of the 3 variations used, namely 0%, 3%, and 5% addition of bamboo fiber roots used did not meet the standard specification of Bina Marga V 2002. 0% was the Marshall Stability value of 898,587kg, FLOW with a value of 2.0 mm, 3 % is with the value of Marshall Stability 592,320kg, FLOW with a value of 2.8 mm, 5% is with a value of Marshall Stability 527,110, FLOW with a value of 4.9 mm.